Sodium Selenosulfate from Sodium Sulfite and Selenium Powder: An Odorless Selenylating Reagent for Alkyl Halides to Produce Dialkyl Diselenide Catalysts - Liu, Yonghong; Ling, Hai; Chen, Chao; Xu, Qing; Yu, Lei; Jiang, Xuefeng (Synlett, 2019)
Na2SeSO3, which can be generated in situ by the reaction of Na2SO3 with Se power, was found to be an odorless reagent for the selenenylation of alkyl halides to produce dialkyl diselenides. These products have been recently shown to be good catalysts for the Baeyer–Villiger oxidation of carbonyl compounds, for the selective oxidation of alkenes, or for the oxidative deoximation of oximes. By using aqueous EtOH as the solvent and avoiding the generation of a malodourous selenol intermediate, the selenylation reaction with Na2SeSO3 is much more environmentally friendly than conventional methods. Owing to the cheap and abundant starting materials and selenium reagents, our novel synthetic method reduces the production costs of dialkyl diselenides as organoselenium catalysts, thereby advancing practical applications of organoselenium-catalysis technologies.
Keywords: dialkyl diselenides; alkyl halides; selenenylation; organoselenium catalysts; green synthesis